Understanding GIS through sustainable development goals: Case studies with QGIS - Holloway, Paul (London CRC Press, 2023)
Understanding GIS through Sustainable Development Goals applies a pedagogical shift to learning GIS, as the readers employ the concepts and methodologies on real-world problems. This book provides 16 case studies across most of the Sustainable Development Goals (SDGs) with step-by-step practical instructions using QGIS(Quantum Geographic Information System) , an open-source software. It helps readers develop GIS skills on real-world data, while learning the fundamentals including spatial data models, projections, and spatial databases, different cartographic methods, such as graduated symbology, change maps, and dynamic visualization, as well as more intermediate and advanced spatial analysis such as geoprocessing, multiple criteria analysis, and spatial statistics. The topics chosen are taught in secondary and tertiary education institutions which make this a textbook for all students and educators.
Keywords: Earth Science; Environmental Studies; Information & Communication Technology (ICT); GIS, Remote Sensing & Cartography; Communication Technology